Thematic Learning Training Based on 2013 Curriculum for Primary School Teachers - Siti Halidjah; Tahmid Sabri; K.Y Margiati; Endang Uliyanti (Universitas Tanjungpura, 2018)
The purpose of this Community Service is to provide an understanding of the implementation of curriculum-based thematic learning. The teachers involved numbered 30 people and were representatives from several schools. The method of the activities carried out in the form of training and counseling by displaying competent speakers and models in terms of compiling and implementing thematic learning based on 2013 Curriculum. The results of community service activities that have been carried out are better understanding of teachers on 2013 curriculum based thematic learning for primaryschool teachers. For teachers who teach in classes that have implemented the 2013 curriculum, this activity can be good learning in order to apply the 2013 Curriculum in the classroom.